Comparative Study of Secondary School Students' and Pre-Service Teachers' Misconception about Simple Electric Circuit - Suryadi, A.; Kusairi, S.; Husna, D. A. (Jurnal Pendidikan Fisika Indonesia, 2020)
The purpose of this study is to compare the misconceptions of secondary school students (junior and senior high school) and pre-service physics teachers about simple electrical circuits.Ã‚Â  The study involved 92 people consisting of 30 junior high school students, 32 senior high school students, and 30 pre-service physics teachers. The diagnostic misconception instrument was adapted from the Simple Electric Circuits Diagnostic Test (SECDT). Data were analyzed by descriptive and inferential analysis. The results of the study indicated that there are 11 misconceptions types that the student had. The clashing current is a type of misconception that is most often found both in high school students and in pre-service teacher. The inferential test showed that there were significant differences of misconception scores among junior high school students, senior high school students, and pre-service physics teachers (KW=12,689, df=2, p< 0.05). Teachers could use the misconception profile as a consideration in planning classroom instruction.